Pengaruh Sistem Full Day School Terhadap Penanaman Sikap Sosial Pada Siswa Di Madrasah Tsanawiyah Negeri 1 Kampar - Alsi Ratu Balqis; Sukma Erni (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This research aimed at finding out the influence of full day school system toward the low social attitudes of students, including the lack of honesty, the lack of discipline, and the lack of full day school system in effective time, at State Islamic Junior High School 1 Kampar. This research was instigated with the lack of honesty for students implementing full day school system and the lack of discipline for students implementing full day school system. It was quantitative research with survey method. All the eighth-grade students at State Islamic Junior High School 1 Kampar were the population of this research, and they were 200 students. The samples were 42% or 84 students selected with random sampling technique. Questionnaire and documentation were the techniques of collecting data. The techniques of analyzing data were descriptive statistical analysis, normality test, linearity test, simple linear regression analysis, product moment correlation analysis, and coefficient of determination with the assistance of SPSS statistics 27. Based on the research findings and data analyses, full day school system that could influence social attitudes in students at State Islamic Junior High School 1 Kampar was in good category with the percentage 75.24%, while instilling social attitudes in students at State Islamic Junior High School 1 Kampar was in good category with the percentage 78.91%. While the correlation test results showed that there was a significant influence of full day school system toward instilling social attitudes in students 0.448 higher than 0.2146 at 5% significant level, so Ha was accepted, and H0 was rejected; and 0.448 higher than 0.2796 at 1% significant level, so Ha was accepted, and H0 was rejected. The percentage of the influence of full day school system toward instilling social attitudes was 20.1%, or the variation of the independent variable used in the model (social attitudes), and the rest 79.9% (100-20.1%) was influenced or explained by other variables.